Impact of Dietary Supplements in Alleviating Human Lifestyle and their Regulatory Aspects - Kalidindi, Venkateswara Raju; Routhu, Shankar; Gopisetty, Dhamasri; Alluri, Phanindra Varma; Nori, Lakshmi Prasanthi (Indian Journal of Pharmaceutical Education and Research, 2024)
Dietary supplements generally items which have the goal of boosting the person's wellness and general well-being and are often ingested at mealtime or in scheduled times in order to improve a person's dietary routine. Once an individual has a nutritional unbalance or as a shortage of certain nutrients, supplementation needs to be taken. Classes of dietary supplements include Vitamins, Minerals, Proteins, Multivitamins, Multiminerals, Herbs, Carbohydrates, hormone activators and oil supplements are present in the form of pill, tablets, capsules and liquids. Supplements should enable individuals having limited nutritional consumption along with effectiveness and also have higher requirements, via strengthening nutrition significance. The risk associated with food supplements, toxicity of the supplements, market trends and future perspectives were also presented. Some include the technical as well as legislative obstacles currently encountered within supplements effectiveness, safety and quality studies. For each country there are separate regulatory approval frameworks and also labelling requirements for the import and export of the food product. So, dietary supplements play a crucial role in every individual.
Keywords: Dietary supplements; Effectiveness; Regulatory approval; Toxicity; Quality; Food; products